(How) Will the Euro Affect Inflation in the Czech Republic? A contribution to the current debate - Tomás Slacík (FIW - Research Centre International Economics, 2008)
In the present study we analyse relevant macro- and microeconomic forces driving inflation in the Czech Republic with a particular focus on how these channels are likely to change in the wake of euro adoption. We employ an ARDL model combined with the Bayesian Model Averaging technique. In order to carry out this analysis, we also estimate the time-varying natural rate of interest purged from the risk premium. Our results suggest that the costs arising from the discontinuation of nominal trend appreciation of the koruna after euro adoption are likely to be rather low. In contrast, a low inflation environment and a harmonization of the business cycles between the Czech Republic and the euro area are essential for ensuring that inflation hikes will remain limited after the euro adoption. The fulfilment of the Maastricht inflation criterion should not be enforced by policy measures that would artificially reduce inflation temporarily. The potential inflationary effect of the changeover cannot be eliminated altogether but it may well be substantially reduced by applying best practices based on the experience of current euro area participants.
Keywords: F31; E31; E43; 330; Euro adoption; inflation; natural rate of interest; Bayesian model averaging; Czech Republic